Market Development Strategies for Fresh Sweet Corn: Findings from 2001 Retailer Surveys - Kimberly Morgan; Robert Degner (EDIS)
In order to better utilize limited marketing dollars, the Fresh Supersweet Corn Council contracted with the Florida Agricultural Market Research Center (FAMRC) in 2001 to conduct surveys of produce retailers and fresh sweet corn consumers. A basic overview of the forces within the industry that determine firm conduct was performed and documented with survey data. This paper presents the retailer survey results, and outlines market development strategies that the Council may utilize to improve year-round consumption of Florida fresh sweet corn. This is EDIS document FE378, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2003.